Anmeldelse af Whatever Happened to Party Government? Controversies in American Political Science - Jensen, Henrik (Politica, 2019)
Mark Wickham-Jones, Whatever Happened to Party Government? Controversies in American Political Science. University of Michigan Press, 2018 (anmeldt af Henrik Jensen)